Inguinal Hernia And Hydrocele In Children - Ida Ayu Wayan Mahayani; Made Darmajaya (E-Jurnal Medika Udayana, 2013)
Inguial hernia and hydrocele is a fairly common disease in children. The study showed that the incidence in the United States reached 10-20 of 1000 live births, with more locations hernia on the right side and 10% bilaterally. Hydrocele is a collection of fluid in the processus vaginalis, and it can cause swelling in the groin or scrotum. Inguinal hernias occur when abdominal organs protrude into the inguinal canal or scrotum. In healthy babies, balls surrounded by a closed room, the tunica vaginalis of the scrotum. In postnatal life, this is a potential space that should not be related to the peritoneum.